Injection Molding Study on the Strength of Weld Line for Polycarbonate and Carbon Fiber Composite Material. Issue 1 (May 2020) - Chung, Chen-Yuan; Yeh, Chin-Chang; Lin, Chia-Min
Abstract: In this study the polycarbonate (PC) and carbon fiber (CF) are used as the experimental materials to investigate the impact of injection molding process parameters on tensile strength of weld line using Taguchi method and response surface methodology. The experiments are conducted via 27 sets of parameter combinations designed based on carbon fiber content, melt temperature, mold temperature, injection speed, injection pressure, packing speed, and packing pressure. The process parameter combination with the highest tensile strength is identified using Taguchi method. Later on, the response surface methodology is used to establish the tensile strength predicting formula formed by process parameters in order to understand the correlation between process parameters and tensile strength. The experimental and analysis results indicate the melt temperature and mold temperature have the most significant impacts on tensile strength.